2011
DOI: 10.1016/j.stem.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Cripto Regulates Hematopoietic Stem Cells as a Hypoxic-Niche-Related Factor through Cell Surface Receptor GRP78

Abstract: Hematopoietic stem cells (HSCs) are maintained in hypoxic niches in endosteal regions of bones. Here we demonstrate that Cripto and its receptor GRP78 are important regulators of HSCs in the niche. Flow cytometry analyses revealed two distinct subpopulations of CD34(-)KSL cells based on the expression of GRP78, and these populations showed different reconstitution potential in transplantation assays. GRP78(+)HSCs mainly reside in the endosteal area, are more hypoxic, and exhibit a lower mitochondrial potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 52 publications
3
135
1
3
Order By: Relevance
“…Interestingly, low oxygen levels stabilize and activate HIF, 44 which is important for the maintenance of hematopoietic stem cells and promotes self-renewal of embryonic stem cells. 45,46 Therefore, the enrichment of hypoxia-, HIF1α-targets and hematopoietic stem cell-associated genes in our AKT-inhibited CD8 + T cells could indicate improved self-renewal capacity and good functionality in low oxygen environments.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, low oxygen levels stabilize and activate HIF, 44 which is important for the maintenance of hematopoietic stem cells and promotes self-renewal of embryonic stem cells. 45,46 Therefore, the enrichment of hypoxia-, HIF1α-targets and hematopoietic stem cell-associated genes in our AKT-inhibited CD8 + T cells could indicate improved self-renewal capacity and good functionality in low oxygen environments.…”
Section: Discussionmentioning
confidence: 92%
“…Cripto is associated with the pluripotent status of both human and mouse ES cells (ESCs) (3), and it acts as a key player in the signaling networks orchestrating ESC differentiation (4). Intriguingly, it has been recently suggested that Cripto may serve as a regulator to control dormancy of hematopoietic stem cells (5).…”
mentioning
confidence: 99%
“…Since the osteoblasts do Cripto is protein that blocks TGF-β signaling is binding with GRP78, also known as HSPA5, on hypoxic HSCs and activate P13K-Akt-pathway leading to the maintenance of HSCs localized in the endosteal niche. Blockade of Cripto-GRP78-signaling by the blocking antibodies N-20 mobilizes HSCs migration from the endosteal region into central part of BM but cannot alter the HSCs number in the BM, peripheral blood and spleen, showing that local mobilization can take place without into the peripheral blood [223]. The endosteal cells expressing Cripto include mostly ALCAM -Sca-1 + and, to a lesser degree, ALCAM -Sca-1 -cells [223].…”
Section: Macrophagesmentioning
confidence: 99%